Math Problem Statement
Without using truth table, show that the following proposition are logically equivalent. (1) p $$$$ \Lambda q(v) (11)~(pV(~pq)p.
Solution
To prove that the propositions and are logically equivalent, we can use logical identities to simplify each expression and show that they ultimately reduce to the same form. Let's proceed with each part separately.
Proposition (I):
Step 1: Distribute over using the Distributive Law
Step 2: Simplify each part using Idempotent and Dominance Laws
- For the first part, , because .
- For the second part, , which still holds.
Thus, simplifies to , which is equivalent to when considered in the same scope.
So, we have:
Proposition (II):
Step 1: Apply Distributive Law
Step 2: Simplify using the Complement Law
- , so the expression becomes:
Step 3: Simplify further using the Identity Law
Since , which reduces to in logical form.
Therefore,
Conclusion
Since both expressions simplify to , we have shown that:
Thus, the two propositions are logically equivalent.
Would you like further details or have any questions?
- How does the Distributive Law apply to logical expressions?
- What role does the Idempotent Law play in simplifying expressions?
- Can logical equivalence be verified using algebraic identities?
- Why does the Identity Law simplify expressions involving ?
- Are there situations where a truth table would be easier for verification?
Tip: Practice identifying when to apply logical laws to simplify expressions without a truth table for faster problem-solving.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Logical Equivalence
Logical Identities
Formulas
Distributive Law
Idempotent Law
Dominance Law
Complement Law
Identity Law
Theorems
Logical Equivalence Theorem
Suitable Grade Level
Undergraduate
Related Recommendation
Proving Logical Equivalence: (p ∧ ¬q) ∨ (p ∧ q) = p Using Distributive, Tautology, and Identity Laws
Logical Equivalence of (¬p ∨ q) ∧ (¬q ∨ p)
Logical Equivalence of (p ∧ q) ∨ (p ∨ q) Without Truth Table
Proof of Logical Equivalence in Boolean Algebra
Proof of Logical Equivalence: p ∨ (¬p ∧ ¬q) ∨ (p ∧ q) = p ∨ (¬p ∧ ¬q)